Analisis Respons Masyarakat Terhadap Program Vaksinasi Covid-19 di Desa Kuala Gunung Kabupaten Batu Bara - Ayu Sukmawati; Rija Aini; Fitri Handayani; Siti Sofiah (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
The vaccination program is one of the efforts made by the Indonesian government to prevent the acceleration of the transmission of Covid-19 in Indonesia. This program continues to be pounded by the government so that the pandemic in Indonesia ends soon so that people's activities return to normal. On the other hand, the community has various responses regarding the program. This study aims to find out how the response of the community in Kuala Gunung Village, Batu Bara Regency, North Sumatra regarding the Covid-19 vaccination program carried out by the government in order to prevent and break the chain of transmission of Covid-19 in Indonesia. The research method used is a qualitative method with data collection techniques through field observations, interviews and documentation in order to sharpen research analysis. Based on the results of the research that has been done, the response of the community in Kuala Gunung Village, Batu Bara Regency is not good enough to the intensified vaccination program. Fear and lack of courage became one of the factors behind people's refusal to be vaccinated and gave an unfavorable response to the intensified program.